Durian Crepe Rabi SugarFlour / Fatin Nurul Arisha Zaini ... [et al.] - Zaini, Fatin Nurul Arisha; Suhaini@Suhaimi, Nur Aida; Anurazni, Afina Syasya; Abdul Razak, Nurshahila; Shafei, Shanorma Amiza (2021)
This business Rabi was started in 2019 and has thrived to this day with the efforts of Bumiputera children who want to venture into business with their spouses. The Durian Crepe Rabi business is run by a former kindergarten teacher known as Puan Rabiatul Adawiyah Binti Ibrahim and assisted by her partner known as Tuan Abdul Halim Bin Abd Rani. Apart from that, in the Durian Crepe Rabi business, it also has a workforce of 20 people and even the number has increased from time to time. Durian Crepe Rabi business is located in Mutiara Damansara known as Rabi SugarFlour Café with full address 48-1, Jalan PJU 7/16, Mutiara Damansara, 60000 Kuala Lumpur, Malaysia. Not only that, this business also has dozens of agents and stockists to further expand the business to be known throughout Malaysia. The couple is also not focused on Durian Crepe only but they also provide a wide variety of cake variations and flavours like Durian Crepe Pandan, Chocolate Batik Cake, Blueberry Cake and many more.